Investigation of Clinical, Laboratory, Imaging Findings and Histopathological Features of Patients wıth Gastric Neuroendocrine Cell Hyperplasia - Çoban, Burcu; Bengi, Göksel; Derviş Hakim, Gözde; Ünlü, Şadiye Mehtat; Kahraman, Dudu Solakoğlu; Barlık, Funda; Kaya, Gamze Çapa; Soytürk, Müjde (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Neuroendocrine cell hyperplasia is a non-neoplastic proliferation of enterochromaffin-like cells and is considered a premalignant lesion because of their potential to progress to neuroendocrine tumor. In this study, we aimed to evaluate the demographic and clinical features, laboratory, radiological and endoscopic findings, gastric biopsy histopathological features, follow-up frequency, and histopathological findings of patients diagnosed with gastric neuroendocrine cell hyperplasia as well as to investigate the factors that play a role in the development of neuroendocrine tumors on the basis of neuroendocrine cell hyperplasia. Materials and Methods: The study has been conducted in 2 centers with 282 patients that were grouped as those with and without neuroendocrine tumor. Individuals with control endoscopy were separated as those with regression of neuroendocrine cell hyperplasia and those without regression, and the determined parameters were evaluated between the groups. Results: The most common histological subtype of neuroendocrine cell hyperplasia was linear+micronodular (50.4%). Neuroendocrine tumor developed in 4.3% (12/282) of the patients with neuroendocrine cell hyperplasia after a mean of 36 months. The presence of polyps as confirmed via endoscopy and dysplasia as confirmed via histopathological examination was significantly higher in favor of the group with neuroendocrine tumor (P = .01). In patients with neuroendocrine cell hyperplasia regressed and patients in whom it did not regress were examined, the rate of asymptomatic patients and increased sedimentation rate were found in favor of the group that did not regress (P = .02 and P = .02), but no difference was found in other parameters. Conclusion: Neuroendocrine tumor development rate was found to be 4.3% in the background of neuroendocrine cell hyperplasia. Two factors predicting progression from neuroendocrine cell hyperplasia to neuroendocrine tumor can be elaborated as the presence of polypoid appearance due to neuroendocrine cell hyperplasia as confirmed via endoscopy and dysplasia as confirmed via histopathological examination Cite this article as: Çoban B, Bengi G, Derviş Hakim G, et al. Investigation of clinical, laboratory, imaging findings and histopathological features of patients wıth gastric neuroendocrine cell hyperplasia. Turk J Gastroenterol. 2024;35(2):92-101.